Analysis of Financial Statements and Their Implications for Corporate Governance in Hajj and Umrah Service Companies - Abd Rochman; Muhammad Irsyad Baitussalam; Moh Affan (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
This study aims to analyze the role of financial statement analysis and its implications for corporate governance in Hajj and Umrah service companies, with a particular focus on PT Haramain Mulia. The study employs a qualitative approach using a literature review method by synthesizing findings from scholarly journal articles, academic books, conference proceedings, and research reports related to financial statement analysis, transparency, accountability, and corporate governance. The literature was collected through systematic searches of academic databases and analyzed using literature reduction, thematic categorization, conceptual synthesis, and theoretical interpretation. The findings indicate that financial statement analysis serves as a strategic instrument for assessing organizational performance through key financial indicators, including liquidity, profitability, solvency, and operational efficiency. Furthermore, financial statement analysis provides essential information for managerial decision-making, risk management, and organizational control. The review also reveals that effective utilization of financial statement analysis contributes significantly to improving transparency, strengthening accountability, reducing information asymmetry, and enhancing corporate governance practices. In the context of PT Haramain Mulia, financial statement analysis supports the responsible management of pilgrims’ funds and strengthens stakeholder trust. The study contributes to the development of corporate governance literature by integrating financial performance, transparency, accountability, and governance mechanisms within the context of faith-based service organizations. Practically, the findings highlight the importance of strengthening financial reporting systems and governance structures to ensure organizational sustainability and public confidence in the Hajj and Umrah industry.